Maqashid Shariah and its Influence on Accountability of the Mosque - Ramadhan, Riza (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
The goal of this study is to investigate the impact of Maqashid Shariah, as represented by accountability, which is the act of being truthful and accountable. Accountability can be related to both of Maqashid Shariah's goals: the first, to protect religion, or Hifdz Ad-Din, and the second, to preserve life, or Hifdz An-Nafs. This study explores the impact of mosque congregants' confidence and engagement in relation to mosque accountability. The impact of the mosque accountability variable on the trust and engagement of congregants is analyzed and tested through a quantitative manner in this study. The population's features are described using a combination of path analysis and descriptive analysis, two types of quantitative analysis. Using Path analysis and the Structural Equation Modeling (SEM) approach, the hyphotesis is tested. Congregants of five significant mosques located in the East Java districts of Lumajang, Jember, Situbondo, Bondowoso, and Banyuwangi make up the research population. This study used five large mosques with 125 members each as its unit of analysis. The quota sampling method is employed in the sampling procedure. The analysis's findings indicate that while participation has a considerable impact on members' involvement, accountability has no discernible effect on members' confidence.